Imaging FlowCytobot modified for high throughput by in‐line acoustic focusing of sample particles. (19th September 2017) - Olson, Robert J.; Shalapyonok, Alexi; Kalb, Daniel J.; Graves, Steven W.; Sosik, Heidi M.
Abstract: Imaging FlowCytobot, a submersible instrument that measures optical properties and captures images of nano‐ and microplankton‐sized particles, has proved useful in plankton studies, but its sampling rate is limited by the ability of hydrodynamic focusing to accurately position flowing sample particles. We show that IFCB's sampling rate can be increased at least several‐fold by implementing in‐line acoustic focusing upstream of the flow cell. Particles are forced to the center of flow by acoustic standing waves created by a piezo‐electric transducer bonded to the sample capillary and driven at the appropriate frequency. With the particles of interest confined to the center of the sample flow, the increased size of the sample core that accompanies increased sample flow rate no longer degrades image and signal quality as it otherwise would. Temperature affects the optimum frequency (through its effect on the speed of sound in water), so a relationship between sample temperature and optimum frequency for acoustic focusing was determined and utilized to control the transducer. The modified instrument's performance was evaluated through analyses of artificial particles, phytoplankton cultures, and natural seawater samples and through deployments in coastal waters. The results show that large cells, especially dinoflagellates, are acoustically focused extremely effectively (which could enable, for example,  > 10‐fold increased sampling rate of harmful algal bloom species, if smaller cells are ignored), while for nearly all cell types typically monitored by IFCB, threefold faster data accumulation was achieved without any compromises. Further increases are possible with more sophisticated software and/or a faster camera.